Determination of uniaxial compressive strength of limestone Određivanje jednoosne tlačne čvrstoće vapnenaca - Vračević, Doris; Dugonjić Jovančević, Sanja; Peranić, Josip; Hodanić, Marko (2019)
The most used parameter in rock engineering practice is the Uniaxial Compressive Strength (UCS). It is often estimated on the field or trough Index-to-strength conversion factors proposed by various researchers for a specific rock type. The research presented in the paper involved field estimation of Uniaxial Compressive Strength using Schmidt rebound hammer and Point Load laboratory testing on limestone rock samples. The results of the estimated UCS were compared to the Uniaxial Compression Strength laboratory testing results on limestone specimens taken from the same location, in order to compare corresponding UCS of limestone rocks. These results can contribute to better estimation of the local design parameters, when direct determination of the UCS in the laboratory is not possible, rather than adopting the values from around the world case studies.
Najčešće korišten parametar u stijenskom inženjerstvu je jednoosna tlačna čvrstoća (UCS). Često se procjenjuje na terenu ili pomoću korelacija s indeksom čvrstoće u točki predloženih od strane različitih istraživača za određen tip stijene. Istraživanja prikazana u radu uključuju terenska ispitivanja jednoosne tlačne čvrstoće Schmidtovim čekićem i laboratorijskog ispitivanja indeksa čvrstoće opterećenjem u točki na uzorcima vapnenačkih stijena. Rezultati procijenjenih UCSa uspoređeni su s laboratorijskim ispitivanjem jednoosne tlačne čvrstoće na uzorcima vapnenaca, uzetih sa iste lokacije, kako bi se usporedili rezultati za odgovarajući UCS vapnenačkih stijena. Ovi rezultati mogu pridonijeti boljoj procjeni lokalnih projektnih parametara kada određivanje točne vrijednosti UCS u laboratoriju nije moguće, no ne i usvajanju vrijednosti dobivenih analizom slučajeva iz ostatka svijeta.
Bibliografija: 37 jed.
Abstract ; Sažetak.
Keywords: Stijenski materijal -- Tlačna čvrstoća -- Vapnenac -- Schmidtov čekić -- Terenska identifikacija